Entrepreneurship in Nursing: an integrative literature review - Fernanda Hannah da Silva Copelli; Alacoque Lorenzini Erdmann; José Luís Guedes dos Santos
ABSTRACT Objective: To demonstrate in the national and international literature the concept and typologies of entrepreneurship in Nursing. Method: Integrative review in six databases, with the descriptors entrepreneurship, entrepreneurs, entrepreneurial, entrepreneurialism, intrapreneurial, iniciativa empresarial, contrato de risco, nursing, nurse, nurses, enfermagem and enfermeira, making a final sample of 31 articles. Results: The concept of entrepreneurship in Nursing is related to personal and professional characteristics, such as autonomy, independence, flexibility, innovation, proactivity, self-confidence and responsibility. The typologies found were: social and business entrepreneurship, and intrapreneurship. Social entrepreneurship is a mechanism of social mobilization and transformation, entrepreneurship is one in which nurses are autonomous professionally and intrapreneurship relates to corporate entrepreneurs. Conclusion: Entrepreneurship can increase the visibility of the profession and foster the creation of new spaces for nurses.